Pembiasaan Berbahasa Arab dan Inggris Untuk Mencetak Generasi Unggul di KMI ASSALAM Bangilan Tuban - Farela, Noviyanti; Putri Sulistyowati, Nadya (Universitas Nahdlatul Ulama Sunan Giri, 2025)
This study examines the Arabic and English language familiarization program at KMI ASSALAM Bangilan Tuban in shaping the nation's next generation to excel amidst the currents of globalization. This descriptive qualitative study focuses on the program's strategy, its impact on students, as well as the inhibiting factors and implemented solutions. Data collection was conducted through participant observation, in-depth interviews with the boarding school supervisor, asatidz, ustadzah, OSPA administrators, and all students, as well as analysis of related documents, with data verification using source and method triangulation. The results of the study identified that the familiarization program was implemented systematically, structured, and scheduled, with full support from all elements of the boarding school. Key strategies included the implementation of a language schedule, daily programs, weekly exercises, and the use of innovative learning media. Significant positive impacts were observed, including drastic improvements in communication skills, language fluency, easier access to authentic religious texts and global knowledge, and the instilling of a foundation for lifelong learning. Despite the lack of awareness of students regarding foreign languages, the boarding school addressed this through measured educational sanctions and close monitoring cooperation between OSPA administrators and room heads. And it can be concluded that the program at KMI ASSALAM has succeeded in transforming potential negative impacts into cognitive and social opportunities, producing students who are not only religious, but also linguistically intelligent, adaptive, and ready to become future leaders in both the spiritual and secular realms.